2005
DOI: 10.1097/01.mlg.0000161341.00258.54
|View full text |Cite
|
Sign up to set email alerts
|

Fungal-Specific Humoral Response in Eosinophilic Mucus Chronic Rhinosinusitis

Abstract: Fungal-specific immunity characterized by serum IgG3 and not IgE, distinguished the EMCRS subgroups from control groups regardless of the presence of fungus within EM or of systemic fungal allergy. Fungal-specific IgE responses in fungal-allergic EMCRS were no different to those in fungal-allergic controls, thus challenging the presumption of a unique pathogenic role of fungal allergy in "allergic fungal sinusitis."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 15 publications
2
75
0
Order By: Relevance
“…Orlandi et al, 369 however, replicated the methods of Shin et al 368 and had opposing results. They found that IL-5 levels correlated strongly with fungal-specific IgE, but did not correlate with fungal-specific IgG as described by Shin et al 368 In a study performed by Pant et al, 370 IgG1 and IgG3 isotypes to fungi were identified in CRS patients with eosinophilic mucin. The effect was independent of IgE sensitivity to fungus.…”
Section: S55mentioning
confidence: 78%
See 3 more Smart Citations
“…Orlandi et al, 369 however, replicated the methods of Shin et al 368 and had opposing results. They found that IL-5 levels correlated strongly with fungal-specific IgE, but did not correlate with fungal-specific IgG as described by Shin et al 368 In a study performed by Pant et al, 370 IgG1 and IgG3 isotypes to fungi were identified in CRS patients with eosinophilic mucin. The effect was independent of IgE sensitivity to fungus.…”
Section: S55mentioning
confidence: 78%
“…359,1078 This has stirred debate regarding AFRS pathophysiology. 370,1072,1076 CRSwNP, including AFRS, often involves a Th2-predominant immune response with eosinophilic inflammation. 1071,1079,1080 Theoretically, the primary stimulus in AFRS is a Type I IgE-mediated hypersensitivity to ubiquitous fungal allergens.…”
Section: Viiig Crswnp and Afrs: Differences In Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…18 Pant et al in his study demonstrated the significance of humoral immunity in the pathogenesis of AFRS. 19 He studied patients with eosinophilic mucin CRS, polypoid rhinosinusitis with or without fungal elements. He stated that elevated levels of fungal-specific IgG3, rather than total serum IgE, is more specific in diagnosing AFRS.…”
Section: Discussionmentioning
confidence: 99%